2021
DOI: 10.1371/journal.ppat.1009703
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric-flow field-flow fractionation of prions reveals a strain-specific continuum of quaternary structures with protease resistance developing at a hydrodynamic radius of 15 nm

Abstract: Prion diseases are transmissible neurodegenerative disorders that affect mammals, including humans. The central molecular event is the conversion of cellular prion glycoprotein, PrPC, into a plethora of assemblies, PrPSc, associated with disease. Distinct phenotypes of disease led to the concept of prion strains, which are associated with distinct PrPSc structures. However, the degree to which intra- and inter-strain PrPSc heterogeneity contributes to disease pathogenesis remains unclear. Addressing this quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Many low-resolution biochemical and spectroscopic comparisons of preparations of different PrP Sc strains have provided evidence of distinct conformations even when strains are formed from the same polypeptide sequence (e.g. (2,(9)(10)(11)(12)(13)(14)(15)(16)(17)). Moreover, PrP Sc strains have been shown to impose their general conformational attributes onto newly recruited PrP molecules in cell-free conversion and amplification reactions (9,18).…”
Section: Introductionmentioning
confidence: 99%
“…Many low-resolution biochemical and spectroscopic comparisons of preparations of different PrP Sc strains have provided evidence of distinct conformations even when strains are formed from the same polypeptide sequence (e.g. (2,(9)(10)(11)(12)(13)(14)(15)(16)(17)). Moreover, PrP Sc strains have been shown to impose their general conformational attributes onto newly recruited PrP molecules in cell-free conversion and amplification reactions (9,18).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the fractions provides information for specific prion preparations regarding hydrodynamic radius allowing one to correlate the relative size of prion particles with infectivity. Cortez et al (2021) demonstrated that two hamster-adapted prion strains with distinct clinical presentation (hyper and drowsy; Bessen and Marsh 1992) differ in the size of the most infectious particle. Interestingly, both PrP Sc aggregates become PK-resistant at the same size.…”
Section: Strainmentioning
confidence: 99%
“…On the initial passage, the incubation period was long and western blot analysis showed two different sized PrP Sc migration patterns. Low titer passage then resulted in the adaptation and selection of two different strains (hyperactive, HY; and drowsy, DY) with significantly different incubation periods and two different PrP Sc structures (Bartz et al 2000;Caughey et al 1998;Safar et al 1998;Cortez et al 2021).…”
Section: Strain Adaptation Selection and Evolutionmentioning
confidence: 99%
“…It is unclear how these differences in strain-specific properties of PrP Sc result in differences in the phenotype of disease. Recent work, however, suggests that PrP Sc particle size can influence prion formation efficiency and PrP Sc clearance and that strain-specific ratios of these PrP Sc particle sizes may provide a mechanistic basis for strain-specific rates of prion formation, incubation period of disease, and tissue tropism [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%